Children's independence Skills Analysis at Low Socioeconomic Environment - Sri Wahyuni; Fadilah, Siti; Bastian, Adolf (Jurnal Pendidikan Usia Dini, 2020)
Research suggests that child independence is more popular in countries with greater wealth and a higher percentage of the educated population. Various research implications expect children's independence and compliance to increase over time in developing countries. This study aims to describe the independence of early childhood who comes from low-income families or at low socioeconomic environment. Using quantitative descriptive, data collection techniques are carried out through a questionnaire. The study population was 30 respondents from the ECE institution who were included in the list of low-income families in 2018, using an area sampling technique. Overall, the teacher stated that all indicators of dependence on children from low-income families had reached the high category, which was 75%. The implication of further research is that aspects of independence in physical abilities, self-confidence, responsibility, discipline, sociability, sharing, and independence in terms of emotional control in early childhood can develop better in a low socio-economic environment. Keywords: Early Childhood, Independence skills, low-socioeconomic environment References [BPS] Badan Pusat Statistik. (2019). Berita resmi statistik. Bps.Go.Id. Amini, M. (2018). Parental Involvement in Improving Independence in Early Childhood. Advances in Social Science, Education and Humanities Research (ASSEHR), 169(Icece 2017), 190–192. https://doi.org/10.2991/icece-17.2018.48 Blair, C., & Diamond, A. (2008). Biological processes in prevention and intervention: The promotion of self-regulation as a means of preventing school failure. Development and Psychopathology, 20(3), 899–911. https://doi.org/10.1017/S0954579408000436 Blair, C., & Raver, C. C. (2015). School Readiness and Self-Regulation: A Developmental Psychobiological Approach. Annual Reviews Psychology, 3(66), 711–731. https://doi.org/10.1146/annurev-psych-010814-015221.School Bridgett, D. J., Burt, N. M., Edwards, E. S., & Deater-deckard, K. (2015). Supplemental Material for Intergenerational Transmission of Self-Regulation: A Multidisciplinary Review and Integrative Conceptual Framework. Psychological Bulletin, 141(3), 602–654. https://doi.org/10.1037/a0038662.supp Brophy-Herb, H. E., Stansbury, K., Bocknek, E., & Horodynski, M. A. (2012). Modeling maternal emotion-related socialization behaviors in a low-income sample: Relations with toddlers’ self-regulation. Early Childhood Research Quarterly, 27(3), 352–364. https://doi.org/10.1016/j.ecresq.2011.11.005 Buckner, J. C., Mezzacappa, E., & Beardslee, W. R. (2009). Self-Regulation and Its Relations to Adaptive Functioning in Low Income Youths. American Journal of Orthopsychiatry, 79(1), 19–30. https://doi.org/10.1037/a0014796 Charilaos, Z., Anastasia, C., Artemis, G., & Dimitrios, S. (2018). The Relationship Between Performance of Neuromuscular Junction and Social Skills (Co-Operation, Interaction, Independence). European Journal of Physical Education and Sport Science, 4(12), 1–20. https://doi.org/10.5281/zenodo.1455997 Cirino, P. T., Miciak, J., Gerst, E., Barnes, M. A., Vaughn, S., Child, A., Huston-Warren, E., Coelho, V., Cadima, J., Pinto, A. I., Guimarães, C., Dark-Freudeman, A., West, R. L., Eisenberg, N., Sulik, M. J., Huh, Y., Reigeluth, C. M., Kim, S., Holloway, S. D., … Cheah, C. S. L. (2018). Attachment and self-regulation. Personality and Social Psychology Bulletin,16(2), 450–467. https://doi.org/10.1177/0022219415618497 Eisenberg, N., Valiente, C., & Eggum, N. D. (2010). Self-regulation and school readiness. Early Education and Development, 21(5), 681–698. https://doi.org/10.1080/10409289.2010.497451 Ellis, B. J., Boyce, W. T., Belsky, J., Bakermans-Kranenburg, M. J., & Van Ijzendoorn, M. H. (2011). Differential susceptibility to the environment: An evolutionary- neurodevelopmental theory. Development and Psychopathology, 23(1), 7–28. https://doi.org/10.1017/S0954579410000611 Evans, G. W., & Kim, P. (2013). Childhood Poverty, Chronic Stress, Self-Regulation, and Coping. Child Development Perspectives, 7(1), 43–48. https://doi.org/10.1111/cdep.12013 Fay-Stammbach, T., Hawes, D. J., & Meredith, P. (2014). Parenting Influences on Executive Function in Early Childhood: A Review. Child Development Perspectives, 8(4), 258–264. https://doi.org/10.1111/cdep.12095 Havighurst, S. S., Wilson, K. R., Harley, A. E., Prior, M. R., & Kehoe, C. (2010). Tuning in to Kids: Improving emotion socialization practices in parents of preschool children-findings from a community trial. Journal of Child Psychology and Psychiatry and Allied Disciplines. https://doi.org/10.1111/j.1469-7610.2010.02303.x Jimenez-Gomez, C., Haggerty, K., & Topçuoǧlu, B. (2020). Wearable activity schedules to promote independence in young children. Journal of Applied Behavior Analysis, 9999(9999), 1–20. https://doi.org/10.1002/jaba.756 Julian, M. M., Leung, C. Y. Y., Rosenblum, K. L., LeBourgeois, M. K., Lumeng, J. C., Kaciroti, N., & Miller, A. L. (2019). Parenting and Toddler Self-Regulation in Low-Income Families: What Does Sleep Have to do with it? Infant Ment Health J., 40(4), 479–495. https://doi.org/doi:10.1002/imhj.21783 Kaya, İ., & Deniz, M. E. (2020). The effects of life skills education program on problem behaviors and social skills of 4-year-old preschoolers. Elementary Education Online, 19(2), 612–623. https://doi.org/10.17051/ilkonline.2020.692983 Lengua, L. J., Moran, L., Zalewski, M., Ruberry, E., Kiff, C., & Thompson, S. (2015). Relations of Growth in Effortful Control to Family Income, Cumulative Risk, and Adjustment in Preschool-age Children. Journal of Abnormal Child Psychology,43(4), 705–720. https://doi.org/10.1007/s10802-014-9941-2 Meylia, K. N., Siswati, T., Paramashanti, B. A., & Hati, F. S. (2020). Fine motor, gross motor, and social independence skills among stunted and non-stunted children. Early Child Development and Care, 0(0), 1–8. https://doi.org/10.1080/03004430.2020.1739028 Nahar, B., Hossain, M., Mahfuz, M., Islam, M. M., Hossain, M. I., Murray-Kolb, L. E., Seidman, J. C., & Ahmed, T. (2020). Early childhood development and stunting: Findings from the MAL-ED birth cohort study in Bangladesh. Maternal and Child Nutrition, 16(1). https://doi.org/10.1111/mcn.12864 Park, H., & Lau, A. S. (2016). Socioeconomic Status and Parenting Priorities: Child Independence and Obedience Around the World. Journal of Marriage and Family, 78(1), 43–59. https://doi.org/10.1111/jomf.12247 Rhoades, B. L., Greenberg, M. T., Lanza, S. T., & Blair, C. (2011). Demographic and familial predictors of early executive function development: Contribution of a person-centered perspective. Journal of Experimental Child Psychology, 108(3), 638–662. https://doi.org/10.1016/j.jecp.2010.08.004 Schmitt, S. A., Mcclelland, M. M., Tominey, S. L., & Acock, A. C. (2014). a self-regulation intervention. Early Childhood Research Quarterly, 1–12. https://doi.org/10.1016/j.ecresq.2014.08.001